SALAFI POLITIK DALAM FASE TRANSISI DEMOKRASI DAN PEMBANGUNAN POLITIK ISLAM STUDI KASUS: TRANSISI POLITIK DI MESIR 2011-2013 - Ibrahim Rantau, Muhammad; Hilman, Hilman; Rahmatullah, Muhammad Asep (QATHRUNÂ, 2024)
The doctrine of salafisme generally believes that involvement in practical politics constitutes bid’ah and falls into the category of hizbiyah which is prohibited in Islam. However, the political transition phase in Egypt in 2011 showed that salafi groups could be involved in islamic politics and again significant votes in the parliamentary elections, as well as being active in the post election political development process. This research aims to show how the salafi groups, effort as an apolitical religious organization are actively involved as an Islamic political force and have a influence on the democratic transition in Egypt. The results of the research show that there have been effort to salafi the Egypt in constitution as wheel as quite sharp conflict in the public sphere of Islamic politics between salafi group and other religious groups, especially traditional Islamic circles (Al-azhar) In formulating concepts and guidelines for Egypt in state life in the transition phase toward democracy.